Poetry of Pavel Zajíček after His Return from Exile - Pilař, Martin (Poznańskie Studia Slawistyczne, 2014)
Pavel Zajíček was a leading personality of Czech rock and literary underground in the 1970s. His imprisonment in 1976 was an important impuls for creation of Charta 77. Communist establishment wanted to get rid of him and therefore (though he was a dissident) he was given his passport and allowed to leave Czechoslovakia for Sweden. In exile he continued in writing and in 1995 he returned to Prague. The present study deals with both invariable and variable qualities of his poetry created after his return. The detailed analysis of his collection of poems called Zvuky sirén a zvonů (The Sounds of Sirens and Bells, 2001) proves that the latest texts of Pavel Zajíček rank among the most original examples of Czech alternative poetry, independent on praised literary tradition.